The Effect of Dosage and Vermicast Types with Different Ingredients as an Organic Fertilizer of Shallot (Alium Ascolonicum L.) - Muktarikan; Arifah, Sri Mursiani; Muhidin; Rasyid, Harun; Zakiya, Aulia (Journal of Tropical Crop Science and Technology, 2024)
Vermicast is a used soil from worm maintenance that is product composting from its maintenance in the form of organic fertilizer and it is very suitable for plants. Vermicast contains various ingredients needed by plants that is hormones such as gibberellins, cytokinins, and auxins, and contains of nutrients (N, P, K, Mg and Ca) and Azotobacter sp. which is a non-symbiotic N-fixing bacterium which can help enrich the N element for plants. In the use of vermicast can be solid or liquid. The purpose of this research is to determine the effect of dosage and vermicast with different ingredients of feed as organic fertilizer for shallot. This research was conducted at the FPP Experiment Garden UMM in Tegalgondo Village with a height of ± 560 m above sea level. The study used a Randomized Block Design with two factors. The first factor: worm feed ingredients (K) consist of (K1); Blotong waste (K2); rumen waste (K3); combination of blotong and rumen waste. The second factor: the dosage of administration (U) consists of (U1); 4 Ton / ha (U2); 5 Tons / ha (U3); 6 Tons / ha (U4); 7 tons / ha. This research included nutrient content in vermicast and on the growth of shallot including: Length of plant, number of leaves, number of tubers, weight of fresh plant, weight of dry plant. The results of this research showed that the dosage and feed ingredients given had no significant effect on plant height parameters, number of leaves, weight of fresh plant, and weight of dry plant of shallot (Alium asconolicum L.) for However it was given significant effect for the height parameters of the plant at the age of 13 HST and the number of leaves at the age of 13 HST. And the best is the combination of K3U3 (Vermicast which is given a combination of blotong and rumen waste feed ingredients) with a dosage of 54 grams / plant.